2018
DOI: 10.1097/md.0000000000009778
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of left main coronary artery disease patients undergoing three different revascularization approaches

Abstract: Significant unprotected left main (LM) coronary artery disease is frequently associated with severe multivessel disease and increased mortality and morbidity compared with non-LM coronary artery disease. This study compared the clinical outcomes of patients with LM disease who received percutaneous coronary intervention (PCI) with stenting, conventional coronary-artery bypass grafting (C-CABG), and robot-assisted CABG (R-CABG).This retrospective study analyzed 472 consecutive LM disease patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Of these, 13 were included in the review. [7][8][9][10][11][12][13][14][15][16][17][18][19] Detailed descriptions of included and excluded studies can be found in Appendix 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 13 were included in the review. [7][8][9][10][11][12][13][14][15][16][17][18][19] Detailed descriptions of included and excluded studies can be found in Appendix 1.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were based on national databases, 10,11 and the remaining 11 studies were singlecentre. [7][8][9][12][13][14][15][16][17][18][19] Patients were selected between 1998 and 2014, and sample sizes ranged from 38 to 966 211. Seven studies compared RCAB to C-CABG, on or off pump, 7,[12][13][14][15][16][17] 3 studies compared RCAB to MIDCAB, [17][18][19] and 1 study compared RCAB to PA-CAB.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigators concluded that PCI remains a fair choice in older patients with low to moderate SYNTAX score and R-CABG is a competent surrogate to standard CABG, with significantly lower duration of intensive care unit and total hospital stay. A similar, retrospective study compared the clinical outcomes of patients with MVD treated either by R-CABG or PCI with DES and reported similar in-hospital and long term-survival rates (follow-up for 5.7 ± 3.0 years, P < 0.001) for both arms, along with commensurate rates of stroke, MI and as expected, significant higher rates of revascularization with PCI (Su et al, 2018(Su et al, , 2019.…”
Section: Novelty-future Directionsmentioning
confidence: 63%